PENGEMBANGAN KNOWLEDGE MANAGEMENT SYSTEM DENGAN METODE DESIGN THINKING DI PT TELKOM INDONESIA (PERSERO) TBK YOGYAKARTA - Budi Suyanto; Gatan Agrasyach D (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2024)
DigiKnow is a Knowledge Management Collaboration Tool that functions as an enabling process for Acquisition, Repository, Sharing & Utilizing Knowledge in TelkomGroup and 12 SOE clusters. But Digiknow is still not working properly so it cannot be used internally by PT. Telkom Indonesia (Persero) Tbk. The Business/System Anlyst has the task of collecting data on the opinions of Telkom employees regarding the Digiknow website and application. After getting the data, we made Crazy 8 based on the opinions we got to generate new ideas that we could develop in this project.